2017
DOI: 10.1016/j.beth.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone–Based Mood Ratings Prospectively Predict Psychotherapy Attendance

Abstract: Objective Psychotherapy non-attendance is a costly and pervasive problem. While prior research has identified stable patient-level predictors of attendance, far less is known about dynamic (i.e., time-varying) factors. Identifying dynamic predictors can clarify how clinical states relate to psychotherapy attendance and inform effective “just-in-time” interventions to promote attendance. The present study examines whether daily mood, as measured by responses to automated mobile phone-based text messages, prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Along with research on overall efficacy and effectiveness of mHealth interventions, studies should assess how to utilize incoming data to predict key clinical events. For example, analyses of daily mood data found that lower mood the day before a therapy session resulted in lower likelihood of attendance [ 41 ]. These types of analytics can inform just in time interventions to improve mHealth and in person interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Along with research on overall efficacy and effectiveness of mHealth interventions, studies should assess how to utilize incoming data to predict key clinical events. For example, analyses of daily mood data found that lower mood the day before a therapy session resulted in lower likelihood of attendance [ 41 ]. These types of analytics can inform just in time interventions to improve mHealth and in person interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, digital apothecaries would highlight for clinicians innovative methods to evaluate their clinical outcomes. Digital tools can provide unique and possibly unobtrusive methods to enhance care (33,34). Technology approaches can provide ongoing treatment assessment, address client adherence/attendance, provide options for peer support, and allow for in-between session client/therapist communication, which can all supplement or enhance the therapeutic process (see Figure 1, type 2, face-to-face augmented with technology).…”
Section: Apothecary Applications For Practicementioning
confidence: 99%
“…Those who received text messages did stay in the study for longer compared with the CBT-only group-13.5 weeks compared with three weeks, respectively. Reporting on a mood monitoring adjunct in this same study, Bruehlmann-Senecal et al [35], assess the predictive capacity of daily mood-monitoring text messages in relation to attendance at a CBT program. Automated daily text messages prompted patients to respond via text with a number corresponding to their mood (on a scale of 1-9).…”
Section: Depression and Mental Health Carementioning
confidence: 99%